Peningkatan Kompetensi Guru TPA LANSIA melalui Metode UMMI dan Metode 10 Jam Belajar Membaca Al-Quran - Akif Khilmiyah; Nurwanto Nurwanto (Jurnal Surya Masyarakat, 2022)
The difficulty experienced by the board members of the Khoirunnisa Taklim Council in managing the elderly TPA is the low motivation and ability to read Al-Quran in elderly women. They complained that the Iqro method used was considered too serious and monotonous so that the mothers had difficulty and lack of enthusiasm in learning to read the Koran. Thus, this service program aims to introduce the Ummi method and the 10-hour learning method of reading Al-Quran for elderly TPA teachers. This service program method is carried out in four stages, namely planning, implementation, technical assistance, and evaluation of service success. The results of this service program show that; (1) Workshops on the Qur'anic learning method using the Ummi method and the 10-hour method have been able to improve the insight and skills of elderly TPA teachers; (2) The 10-hour Quran reading learning method is more desirable than the UMMI method because it is free and easy to implement. Meanwhile, Ummi's method was considered too procedural and expensive to follow; (3) The 10-hour learning method for reading the Koran is proven to be effective in increasing the motivation of elderly mothers in learning to read the Koran because the material is easily accessible, shared, and practical. The implication of this service for the community is that in learning Al-Quran, it must prioritize the elements of fun, convenience, and according to the age of the students.